2022
DOI: 10.1111/add.16072
|View full text |Cite
|
Sign up to set email alerts
|

The effect of prenatal cannabis exposure on offspring preterm birth: a cumulative meta‐analysis

Abstract: Background and aims Mixed results have been reported on the association between prenatal cannabis exposure and preterm birth. This study aimed to examine the magnitude and consistency of associations reported between prenatal cannabis exposure and preterm birth. Methods This review was guided by the Preferred Reporting Items for Systematic Review and Meta‐Analysis (PRISMA) guidelines. We performed a comprehensive search of the literature on the following electronic databases: PubMed, EMBASE, SCOPUS, Psych‐INFO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…This is likely due to the premature birth that was observed. This premature birth is like what is seen in human studies of prenatal cannabis exposure, and the sex differences seen follow the trend where male animals are affected more strongly by teratogens than female animals (237,256).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This is likely due to the premature birth that was observed. This premature birth is like what is seen in human studies of prenatal cannabis exposure, and the sex differences seen follow the trend where male animals are affected more strongly by teratogens than female animals (237,256).…”
Section: Discussionsupporting
confidence: 68%
“…This may cause some people to see it as a suitable treatment for morning sickness, since it is approved for nausea treatment in cancer care (234). And while it is true that fatal overdoses from cannabis use have never been reported, human studies are emerging which show that in utero exposure to THC, the psychoactive component of cannabis, is correlated with negative psychiatric outcomes and premature birth (235)(236)(237). Approximately 2% of pregnant people report using cannabis, a number that is comparable to alcohol (213).…”
Section: Introductionmentioning
confidence: 99%
“…For many, pregnancy is a key time to make changes to substance use, and many pregnant persons successfully quit by the third trimester (Ebrahim & Gfroerer, 2003). However, use of cannabis and tobacco products is prevalent among pregnant and postpartum individuals and may increase health risks for both the pregnant person and child (De Genna et al, 2019; Duko et al, 2023). Prior initial studies suggested that co-use of cannabis and tobacco may lead to greater likelihood of substance use in pregnancy or at postpartum (Coleman-Cowger et al, 2017; De Genna et al, 2018; England et al, 2020; Ko et al, 2020; Qato et al, 2020); results from the present study extend this literature by demonstrating that women who endorse prepregnancy co-use are less likely to achieve cessation during pregnancy and are more likely to relapse to use of cannabis/tobacco into the postpartum period.…”
Section: Discussionmentioning
confidence: 99%
“…For example, among pregnant individuals, cannabis and tobacco co-use is up to three times more common than cannabisonly use (Coleman-Cowger et al, 2017;Ko et al, 2018), a majority of pregnant individuals who smoke cigarettes also report use of cannabis (Ko et al, 2015), and women who report co-use in pregnancy are more likely to continue using both or either substance during pregnancy or postpartum (Coleman-Cowger et al, 2017;De Genna et al, 2018;England et al, 2020;Ko et al, 2020;Qato et al, 2020). Use of tobacco or cannabis across the perinatal period is associated with numerous negative birth outcomes, such as low birth weight, premature birth, respiratory illness, cognitive deficits, and increased secondhand smoke exposure (Centers for Disease Control and Prevention, 2001;Duko et al, 2023;Lin et al, 2023;Regan et al, 2021), with co-use associated with worse neurobehavioral and birth outcomes (Coleman-Cowger et al, 2018;De Genna et al, 2019;Layoun et al, 2022;Stroud et al, 2018Stroud et al, , 2020.…”
mentioning
confidence: 99%
“…Many studies have consistently reported that prenatal cannabis use is associated with an increased risk of preterm birth, defined as delivery before 37 weeks' gestation, even after adjusting for confounders such as tobacco use. [9][10][11][12]152 In general, most studies reported the results of any preterm birth, but only a few stratified results by spontaneous versus indicated preterm births.…”
Section: Preterm Birthmentioning
confidence: 99%